The Lockdown Impact on the Relations between Portuguese Parents and Their 1- to 3-Year-Old Children during the COVID-19 Pandemic - Vian, Frederica (2022)
Funding Information: In Portugal, during the first lockdown, with few exceptions, families with children under 12 years old were given a choice. One parent could suspend his/her professional activity temporarily and receive financial support from the National Social Security System []. Most families, especially those with little children, chose this option. Publisher Copyright: © 2022 by the authors.